Conflict management of construction projects – a case study Kuwait International Airport Cargo City - Alazemi, Mohammad KhTh E; Mohiuddin, A. K. M.; Al-Juboori, Salloom A. (International Academy of Science, Engineering and Technology (IASET), 2019)
Exchanges within the construction teams have been often found to be argumentative, conflict and crisis ridden, and as a result individual worker in the industry are exposed to extreme hostility. These conflicts result from disagreements about ways of solving spot site-related problems, insufficient planning, ill-prepared contract documents,and the lack of coordination between the contracting parties. Members in a construction project tend to form a community with an intricate set of intertwined relationships. Continuing conflicts among members therefore manifest in further disagreements that can ruin a project, and result in thorny litigation, amplified cost, collapse in communication, and strained task conveyance. This study therefore seeks to discover the causes of such conflicts within the construction sector, and the ways by which these conflicts are resolved. Quantitative design has been used in combination with a cross-sectional questionnaire directed at conflict management of construction projects at the Kuwait international airport. A total of 188 questionnaires have been distributed, out of which 14 were lost, and 11 of them have not been answered. Responses of 163 participants were recorded and analyzed through the use of the Statistical Package for Social Scientists (SPSS). To fix the correspondence issue, the study involved follow-ups of the project status using the digital platform of BIM software in form of progress reports, site reporting, and meeting site project team. Results show that the conflict management strategy of construction project related strongly with employee’s situation, efficiency, law, development, and growth restrictions on investment income at Kuwait project construction sites. The conflict management strategy of construction project was found to have a positive effect on the performance of the workers in construction projects with Beta Coefficient = 0.904;indicating that for one-unit increase in conflict management strategy, the performance of construction projects in Kuwait International Airport Cargo City would increase by 0.904 unit. Finally, when participants were asked if there is a delay in project or not, 63.2% of the total sample answered [Yes] as the highest percent, while 16.6% of the total sample answered by [No] and 20.2% didn't know.